Rapid onset of molecular friction in liquids bridging between the atomistic and hydrodynamic pictures - Straube, Arthur V.; Kowalik, Bartosz G.; Netz, Roland R.; Höfling, Felix (Communications physics, 2020)
Friction in liquids arises from conservative forces between molecules and atoms. Although the hydrodynamics at the nanoscale is subject of intense research and despite the enormous interest in the non-Markovian dynamics of single molecules and solutes, the onset of friction from the atomistic scale so far could not be demonstrated. Here, we fill this gap based on frequency-resolved friction data from high-precision simulations of three prototypical liquids, including water. Combining with theory, we show that friction in liquids emerges abruptly at a characteristic frequency, beyond which viscous liquids appear as non-dissipative, elastic solids. Concomitantly, the molecules experience Brownian forces that display persistent correlations. A critical test of the generalised Stokes–Einstein relation, mapping the friction of single molecules to the visco-elastic response of the macroscopic sample, disproves the relation for Newtonian fluids, but substantiates it exemplarily for water and a moderately supercooled liquid. The employed approach is suitable to yield insights into vitrification mechanisms and the intriguing mechanical properties of soft materials. How friction in liquids emerges from conservative forces between atoms is currently not well-understood, but it is a crucial parameter for dynamic processes in liquid matter. Here, the authors combine frequency-resolved simulation data with theory to show that the friction felt by a single molecule occurs abruptly below a certain frequency.